Bibliotherapy for Emotional Literacy - Latifah, Leny (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2019)
One way to help teens manage their emotions is by using emotional literacy. Emotional literacy is a person's ability to understand, express emotions to people, respond to the expression of the feelings of others, and take responsibility for their actions. Emotional literacy can be done through pedagogical strategies, as well as the use of the application of theory and various other learning strategies. Counselors need a method to develop emotional literacy skills in students either by media bibliotherapy or better known as biblikonseling. In this case, the counselor gave the book or story. The utilization of the book as a medium of therapy is called bibliotherapy. Bibliotherapy is psychotherapeutic support through reading material to help someone who is experiencing personal problems. This treatment method is highly recommended, especially for patients who are challenging to express issues verbally. The subjects were students' Universitas Kanjuruhan Malang Department Guidance and Counseling in 2015, 2016. The reason for choosing Guidance and Counseling Student Universitas Kanjuruhan Malang, as guidance and counseling student, is a candidate for school counselors, and they are required to have a good personality and need to be developed early on. This study aims to determine the effectiveness of bibliotherapy techniques to improve the skills of emotional literacy student guidance and counseling Universitas Kanjuruhan Malang. The method used in this study is the technique of pre-experimental design with one group pretest-posttest design. This design is a design study to test the effectiveness of a treatment on an individual basis.